ANALISIS PENGENDALIAN KUALITAS PRODUK PIVOT PLATE PADA PROSES ASSEMBLY DI PT SIMATELEX MANUFAKTUR BATAM - Ritonga, Bintang; Sirait, Ganda (Computer Science and Industrial Engineering, 2025)
PT Simatelex Manufacturing, located in Batamindo Industrial Park, Batam, specializes in producing household appliances, beauty tools, and robotics. Among the key components they assemble is the pivot plate, which which works as a filter, opener, pod wrapper, and hot water channel. The issue explored in this research is the defect rate of pivot plates, which often surpasses the company’s acceptable limit of 1%. The goal of this study is to assess the pivot plate’s quality, uncover the root causes of defects, and offer solutions to minimize them. To do this, researchers used the Failure Mode and Effect Analysis (FMEA) method, along with supporting tools such as the 5W+1H approach, P charts, and a fishbone diagram. The analysis revealed several main causes: overheating machines (RPN 288), workers rushing during tasks (RPN 192), product build-up (RPN 150), inefficient workstation layout (RPN 180), and fragile materials (RPN 144). To reduce these issues, the study suggests routine machine maintenance, clear work instructions, improved layout planning, and material inspections every two hours by QC. These strategies aim to lower the defect rate and enhance the overall quality of the pivot plate, contributing to better production performance.